The colour preference of scalloped spiny lobster, Panulirus homarus. Issue 1 (April 2021) - Lesmana, D; Supriyono, E; Junior, M Z; Nirmala, K; Jusadi, D
Abstract: The background colour of a tank can affect the intensity of light that is absorbed or reflected. The objective of this research is to evaluate the colour preference of the scalloped spiny lobsters. Colour preference observations were carried out every half hour for 24 h. The result showed the spiny lobster had a consistent preference for black background (> 35%) and aversion to yellow, white, blue, and green background (P <.05) in the day. In the dusk, the spiny lobster had a consistent preference for red background(> 25%) and aversion to black, yellow, white, blue, and green background (P > .05). In the night, the spiny lobster had a consistent preference to red background (> 30%) and aversion to white and yellow background (P <.05). The number of lobsters moving towards the red tank continues to increase in the night rather than the dusk. Nocturnal activity is still going on the dawn.